Physicochemical Property-Driven Optimization of Diarylaniline Compounds as Potent HIV-1 Non-Nucleoside Reverse Transcriptase Inhibitors - Liu, Na (2014)
Using physicochemical property-driven optimization, twelve new diarylaniline compounds (DAANs) (7a–h, 11a–b and 12a–b) were designed and synthesized. Among them, compounds 12a–b not only showed high potency (EC(50) 0.96–4.92 nM) against both wild-type and drug-resistant viral strains with the lowest fold change (FC 0.91 and 5.13), but also displayed acceptable drug-like properties based on aqueous solubility and lipophilicity (LE > 0.3, LLE > 5, LELP < 10). The correlations between potency and physicochemical properties of these DAAN analogues are also described. Compounds 12a–b merit further development as potent clinical trial candidates against AIDS.